2018
DOI: 10.1186/s11671-018-2502-9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 20.19% Efficient Single-Crystalline Silicon Solar Cell with Inverted Pyramid Microstructure

Abstract: This paper reports inverted pyramid microstructure-based single-crystalline silicon (sc-Si) solar cell with a conversion efficiency up to 20.19% in standard size of 156.75 × 156.75 mm2. The inverted pyramid microstructures were fabricated jointly by metal-assisted chemical etching process (MACE) with ultra-low concentration of silver ions and optimized alkaline anisotropic texturing process. And the inverted pyramid sizes were controlled by changing the parameters in both MACE and alkaline anisotropic texturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Inverted pyramid (IP) as an attractive light-trapping structure has attracted considerable attention due to its superior antireflection effect and structural characteristics [1][2][3][4][5][6][7]. To be specific, the incoming short-wavelength light in silicon (Si) IP undergoes triple or more bounces before being reflected away, possessing one or more bounces than that in traditional upright pyramids [7][8][9]. Meanwhile, this inverted pyramid-structured Si will avoid severe recombination losses faced by the nanostructured black Si [10][11][12][13][14][15][16] because of its big and open structural characteristic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inverted pyramid (IP) as an attractive light-trapping structure has attracted considerable attention due to its superior antireflection effect and structural characteristics [1][2][3][4][5][6][7]. To be specific, the incoming short-wavelength light in silicon (Si) IP undergoes triple or more bounces before being reflected away, possessing one or more bounces than that in traditional upright pyramids [7][8][9]. Meanwhile, this inverted pyramid-structured Si will avoid severe recombination losses faced by the nanostructured black Si [10][11][12][13][14][15][16] because of its big and open structural characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing Cu nanoparticles to catalyze chemical etching of Si, Yang et al [8] have achieved 18.87% efficient IP-structured Si solar cells with a large area. Zhang et al [9] have fabricated sc-Si solar cell with IP microstructure by modulated alkaline texturing combined with an optimized MACE method and have achieved a 20.19% efficient 1-μm-sized IP-textured device with a large area. So far, the performances of Si IP solar cell with a large area are not yet satisfied suffering from the large-area uniformity of IP morphology, the control of the IP feature size, and the passivation of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some achieves have shown that nanostructure with gradually changed sidewall profiles can effectively improve the optical performance of the solar cells [19]- [22]. Guan Zisheng et al made an inverted pyramid structured c-Si solar cell by controlling the metal assisted chemical etching process, which improved the Jsc by 0.22 mA/cm 2 when comparing with the best positive pyramid structured c-Si solar cell [20]. Fan Zhiyong et al used the pre-imprinting anodization AAO (PIA-AAO) process to prepare amorphous silicon solar cells on nano-cone plastic substrates, the light trapping efficiency reached as high as two folds of the similar planar devices [21].…”
Section: Introductionmentioning
confidence: 99%
“…The industrial production of sc-Si solar cells is generally based on the texturization of upright pyramid structures through alkaline etching techniques to reach an average reflectivity of 10~15% [14]. But due to recent innovations, the inverted pyramid (IP) structure is being explored as a viable alternative because of its comparatively higher light trapping capability and lower specific surface area [15].…”
Section: Introductionmentioning
confidence: 99%